Kesadaran masyarakat dalam menjaga kebersihan lingkungan - Muhammad Alif Fidia; Fatmariza Fatmariza; Henni Muchtar; Eni Kurniawati (Journal of Education, Cultural and Politics, 2026)
Public awareness in maintaining environmental cleanliness is one of the essential elements in the implementation of civic responsibility at the local level. In Nagari Sicincin, Padang Pariaman Regency, environmental cleanliness remains a significant issue, as evidenced by the community’s habit of disposing of waste indiscriminately in public places such as markets, roadsides, and drainage channels. This study adopts a qualitative approach with a descriptive method to analyze the ongoing social phenomena. Data were collected through observation, in-depth interviews, and documentation, involving community members, community leaders, and village officials as informants. The results of the study indicate that the lack of public awareness is influenced by both internal and external factors. Internal factors include indifferent attitudes, laziness, and the perception that cleanliness is solely the responsibility of the government. Meanwhile, external factors include inadequate infrastructure, limited cleanliness programs, and weak socialization and law enforcement. The consequences of this situation are environmental degradation, increased health risks, and disruptions to community social activities. Therefore, collaborative efforts are needed through environmental education, the provision of adequate facilities, and the strengthening of civic responsibility values to create a clean, healthy, and sustainable environment.